Placenta Previa and the Associated Risk Factors - Saira Nazneen, Naila Bukhari (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Placenta previa is a key risk factor for obstetric bleeding, which is a primary factor of feto-maternal mortality and morbidity. The main goal of this study is to estimate the prevalence of placenta previa, along with secondary goals of evaluating the risk factors associated with this condition. The outcome of this study will assist in determining future efforts and assessment needs. Methods: From April 2021 to February 2022, an observational cross-sectional study was conducted at khyber teaching hospital peshawar MTI. During the study period, all pregnant women between 18 to 40 years of age who visited the hospital’s outpatient’s department were included. Results: The incidence of placenta praevia was found to be 2.2%. The most affected age group was >35 years. Previous caesarean section, increasing maternal age and multiparity (>4) were the significant risk factors (P < 0.05). Conclusions: Multiparity, previous caesarean section and increasing maternal age were statistically associated with placenta previa. Keywords: Placenta Previa, Caesarean Section, Risk factors, Multiparity